Potensi Ekstrak Daun Pala (Myristica Fragrans Houtt) Sebagai Pengawet Alami Terhadap Kualitas Daging Ayam Broiler - Ratna Widyawati; Nurul Hidayah; Wardhani Lailia Dwi Kusuma; Marsela Irnawati Nuwa (Jurnal Ilmiah Fillia Cendekia, 2020)
The purpose of this study was to determine the potential of nutmeg leaf extract (Myristica fragrans houtt) on organoleptic (color, smell, texture), pH value, and Total Plate Count (TPC) of broiler chicken meat. The experimental design used in this study was a randomized complete design with 4 treatments and 6 replications namely P0 (control), P1 (nutmeg leaf concentration 20%), P2 (nutmeg leaf concentration 30%), P3 (nutmeg leaf concentration 40%) on broiler chicken meat that was marinated for 30 minutes and allowed to stand for 24 hours. Data of organoleptic test used Kruskal Wallis analysis. P3 increased the color of the meat with an average ranking of 90,00, suppressed the smell of meat with an average ranking of 104,50, and maintained the texture of the meat with an average ranking of 82,05. The pH and Total Plate Count (TPC) tests used statistical analysis of the Analysis of Variants. The average pH value at P1 was 6,6917, P2 was 6,3750, P3 was 5,9250. The average Total Plate Count (TPC) at P1 was 5,1×103, P2 was 1,1×103, P3 was 0,6×103. Statistical analysis showed that nutmeg leaf extract significantly affected organoleptic, pH value, and Total Plate Count (TPC) of broiler chicken meat (P<0,05). The conclusion of this study was that the concentration of 40% has the most potential for organoleptic, pH values ​​and Total Plate Count (TPC).